Lessons for collaborative research in a changing operating environment. (May 2017) - Dovers, Stephen; Whinam, Jennie; Krogh, Martin; Young, Ann; Crawford, Mary‐Anne
Summary: This Comment records the details of an unusual multipartner ecological research programme studying Temperate Highland Peat Swamps on Sandstone in the Sydney Basin‐Blue Mountains area of New South Wales. We draw lessons from the experience of designing and managing this multipartner ecological programme, which was based on a nontraditional funding source – that is an enforceable undertaking required of a coal mining company related to an occurrence at a mine site. The research programme encompassed geomorphology, ecohydrology and ecology of a number of sites. Given the currently constrained public‐good environmental research funding and pressures for both researchers and managers to find new, collaborative ways of funding and implementing research, lessons drawn from such innovative experiences may be of wider utility. In particular, lessons are drawn from the programme regarding the time required to design collaborative processes and the need for explicit programme management capacities.